Kemiskinan yang Menguntungkan: Analisis Kritis Program BLT di Desa Sumengko Kabupaten Nganjuk - M. Abu Dzar Al-Ghifari; Dewien Nabielah Agustin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This article critically examines the implementation of the Village Fund Direct Cash Assistance (BLT-DD) program in Sumengko Village, Nganjuk Regency, using Herbert Gans’ theory of the latent functions of poverty. Employing a descriptive qualitative approach, the research is based on in-depth interviews with recipients, village officials, and community leaders, as well as literature review and local documents. The findings reveal that although BLT-DD was designed as a social protection measure during the COVID-19 pandemic, in practice it has reinforced social inequality, created economic dependency, and strengthened the symbolic control of village elites over citizens. The distribution process often lacks transparency and public participation, positioning the poor as passive recipients with little room to engage or question. The program also serves as a tool for political legitimization, particularly in the context of local electoral politics. These findings support Gans’ argument that poverty performs hidden functions benefiting dominant groups—economically, politically, and symbolically. Thus, poverty in rural areas is not merely a result of structural disparities but is actively maintained through organized social mechanisms. The study recommends a transformation of social assistance policies toward more participatory and empowering models beyond short-term charity